Supraparticles for Sustainability. (1st February 2021) - Wintzheimer, Susanne; Reichstein, Jakob; Groppe, Philipp; Wolf, Andreas; Fett, Bastian; Zhou, Huanhuan; Pujales‐Paradela, Rosa; Miller, Franziska; Müssig, Stephan; Wenderoth, Sarah; Mandel, Karl
Abstract: The indispensable transformation to a (more) sustainable human society on this planet heavily relies on innovative technologies and advanced materials. The merits of nanoparticles (NPs) in this context are demonstrated widely during the last decades. Yet, it is believed that the impact of particle‐based nanomaterials to sustainability can be even further enhanced: taking NPs as building blocks enables the creation of more complex entities, so‐called supraparticles (SPs). Due to their evolving phenomena coupling, emergence, and colocalization, SPs enable completely new material functionalities. These new functionalities in SPs can be utilized to render six fields, essential to human life as it is conceived, more sustainable. These fields, selected based on an entropy‐rate‐related definition of sustainability, are as follows: 1) purification technologies and 2) agricultural delivery systems secure humans "fundamental needs." 3) Energy storage and conversion, as well as 4) catalysis enable the "basic comfort." 5) Extending materials lifetime and 6) bringing materials back in use ensure sustaining "modern life comfort." In this review article, a perspective is provided on why and how the properties of SPs, and not simply properties of individual NPs or conventional bulk materials, may grant attractive alternative pathways in these fields. Abstract : Assembly of nanoparticles (NPs) to more complex entities, so‐called supraparticles (SPs), yields functionalities that cannot be achieved with individual NPs alone. Particularly in fields that contribute to sustainability (of which a definition is given in this article), the unique functionalities of SPs are very useful and promise great application potential in the future.